The Role of Maritime Trade in Shaping the Historical Footprint of Economic and Cultural Dynamics: A Case Study on the Medieval Silk Road - Ursula seventry, Maria (Journal Social Humanity Perspective, 2023)
This research aims to investigate the influence of maritime trade on the economic and cultural developments along the Medieval Silk Road. Employing a case study approach, the study focuses on the impact of trade routes, specifically the Silk Road, during the Middle Ages. The methodological framework includes archival research, analysis of historical documents, and archaeological findings. By examining the interconnectedness of regions through maritime trade, the research seeks to unravel the intricate web of economic and cultural exchanges that occurred along these routes. The anticipated results aim to contribute valuable insights into the historical dynamics, shedding light on the transformative effects of maritime trade on societies and civilizations during this significant period.